2014
DOI: 10.1007/s00266-014-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Large-Volume Liposuction for Obese Healthy Women: A Meta-Analysis of Fasting Insulin Levels

Abstract: Many beneficial metabolic effects resulting from dermolipectomy and liposuction procedures are described in the literature. In particular, fasting plasma insulin and thus insulin sensitivity seem to be positively influenced. Further research, including prospective clinical studies, is necessary for better exploration of the effects that body-contouring plastic surgery procedures have on metabolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Liposuction has its advantages and disadvantages. In the case of healthy, obese women, a significant reduction in fasting plasma insulin resulting from large-volume liposuction has been reported (Boriani et al, 2014), while in women with normal weights, liposuction downregulates adiponectin subcutaneous adipose tissue (scAT) gene expression and serum levels and upregulates scAT gene expression of inflammation-related genes six months after surgery, irrespective of exercise training (Yazigi Solis et al, 2014). In addition, it has been suggested that using liposuction in the overall treatment of obesity could lead to an improvement in insulin sensitivity and thus greatly improve an obese patient's quality of life (Perez, 2007).…”
Section: Lipotourism: Active Leisure Tourism?mentioning
confidence: 99%
“…Liposuction has its advantages and disadvantages. In the case of healthy, obese women, a significant reduction in fasting plasma insulin resulting from large-volume liposuction has been reported (Boriani et al, 2014), while in women with normal weights, liposuction downregulates adiponectin subcutaneous adipose tissue (scAT) gene expression and serum levels and upregulates scAT gene expression of inflammation-related genes six months after surgery, irrespective of exercise training (Yazigi Solis et al, 2014). In addition, it has been suggested that using liposuction in the overall treatment of obesity could lead to an improvement in insulin sensitivity and thus greatly improve an obese patient's quality of life (Perez, 2007).…”
Section: Lipotourism: Active Leisure Tourism?mentioning
confidence: 99%
“…Although the reduction of subcutaneous fat alone does not lead directly to reduction of cardiovascular risk in obese subjects 4 , there is some evidence that the large-volume liposuction might positively influence the insulinemia 5 and thus insulin sensitivity. Furthermore, clinical experience shows that aesthetic procedures leading to improved patient’s self esteem 6 often significantly enhance the motivation to further lifestyle changes towards healthier goals.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Boriani et al regarding the metabolic effects of large volume liposuction (LVL) and their meta-analysis of fasting insulin levels [1]. They reported beneficial metabolic effects from their literature review of 14 eligible studies.…”
mentioning
confidence: 99%